The Effect of ÔÇ£Kids ModerationsÔÇØ Interactive Multimedia on Religious Moderation Attitudes in Early Childhood - Fahrun Nisak, Farahh; Munawaroh, Hidayatu; Abbas, Salbia (Indonesian Journal of Early Childhood Educational Research (IJECER), 2022)
This research aims to determine the effect of interactive multimedia on religious moderation attitude in early childhood. The research used quasi-experimental method. One group pretest posttest was chosen as the design of the research. Data were collected by using checklist observation and analyzed using t-test. Results showed that religious moderation attitude in early childhood was increased by applying ÔÇ£Kids ModerationsÔÇØ interactive multimedia in learning process. Therefore, multimedia can be used as a tool to introduce religious moderation attitude since an early age and prevent intolerance as a root of radicalism in the future.